Analysis of the content of Arabic language courses for the secondary stage; Scientific and administrative track in the Kingdom of Saudi Arabia in light of the theory of multiple intelligences - Alsweerky, Muhammad Ali Hassan (Journal of Educational and Psychological Sciences, 2020)
The aim of this study was to identify the degree of inclusion, distribution and balance of multiple intelligences indicators in Arabic language courses for the secondary stage. The scientific and administrative track in Saudi Arabia was represented by units of analysis (activities and questions). To achieve the objectives of the study, The sample consists of four courses for the Arabic language for the secondary stage, with a total of 254 activities and 146 questions. The results of the analysis of the activities and the questions together revealed that the intelligences (linguistic, logical, and social) had an average of 51.6%, 18.9% and 10.5% respectively, The rest of the intelligences were: (physical 6.4%, spatial 3.8%, natural 2.9%, music 2.8%, self-2.3%), all of which were very low, 48,4%, logical intelligence at 20.9%, all of them very high, and the rest of the intelligences came at very low rates, and the results of the analysis of the questions got linguistic intelligence at 58.8%, logical intelligence at 14.9% , And The number of different intelligences was unevenly distributed over these courses. In the light of the results revealed by the study, a number of recommendations and proposals were presented to achieve the required balance in Arabic language courses and courses.